Environmentally Friendly Polymers and Polymer Composites (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Continuous research advances have been observed in the field of environmentally-friendly polymers and polymer composites due to the dependence of polymers on fossil fuels and the sustainability issues related to plastic wastes. This book compiles the most recent research works in biopolymers, their blends and composites, and the use of natural additives, such as vegetable oils and other renewable and waste-derived liquids, with their marked environmental efficiency devoted to developing novel sustainable materials. Therefore, Environmentally Friendly Polymers and Polymer Composites provides an overview to scientists of the potential of these environmentally friendly materials and helps engineers to apply these new materials for industrial purposes.